#Skinny girls: young girls' learning processes and health-related social media. Issue 1 (2nd January 2022) - Goodyear, Victoria; Andersson, Joacim; Quennerstedt, Mikael; Varea, Valeria
ABSTRACT: This paper provides in-depth knowledge into young girls' learning processes in relation to physical activity, diet/nutrition and body image. Data were generated from interviews with 49 girls (age 13–15) in England. The practical epistemological analysis technique was used to explore young people as both producers and consumers, or prosumers, of content and knowledge. The data illustrate that adolescent girls navigate two interrelated health-related paradoxes within publicly private spaces: (i) skinny fat and (ii) naturally fake. Skinny fat refers to how participation in social media represents a continuous struggle of becoming skinny, but at the same time not trying too hard to become too skinny. Naturally fake refers to how having a 'natural' look is highly valued, but equally, it is acceptable to be 'fake'. Overall, adolescent girls are competent users of social media, who are able to navigate the complexity of the medium and its contents. At the same time, the adolescent girls sometimes found themselves, unintentionally, exposed to risks (e.g. bullying or body dysmorphia), particularly when social media was experienced publicly in a temporal order, connected to the past or present, and without control of potential future effects and impacts. Relevant adults should acknowledge young people's vast competence of life on social media and further empower young people to self-regulate their learning through social media, and in ways that help them to learn from experiences about their health and bodies to shape future actions.